1977
DOI: 10.1139/z77-158
|View full text |Cite
|
Sign up to set email alerts
|

The ectoparasites of three species of seabirds from Newfoundland, Canada

Abstract: Two groups of ectoparasites, namely Mallophaga and Acarina, were recovered from 47 Larus argentatus, 29 Rissa tridactyla, and 18 Oceanodroma leucorhoa taken on Gull Island, Witless Bay, Newfoundland, during the period June–August 1974. Mallophaga of the genera Saemundssonia and Quadraceps (Ischnocera) were found to be common ectoparasites of both L. argentatus and R. tridactyla and the genera Halipeurus (Ischnocera) and Austromenopon (Amblycera) were recovered from O. leucorhoa. A single ixodid tick, Ixodes (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…All seabird species examined in this study hosted at least three feather mite species, with Cape Verde shearwaters and Bulwer's petrels presenting the richest mite communities (eight species each). This number is in line with mite richness documented in other groups of birds, including seabirds (Fitzpatrick and Threlfall, 1977;Doña et al, 2016). For instance, other procellariiform seabirds are known to harbor more than one mite species: Puffinus gravis (nine), Oceanodroma leucorhoa (eight), and Puffinus tenuirostris (seven) (Bourgeois and Threlfall, 1979;Doña et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…All seabird species examined in this study hosted at least three feather mite species, with Cape Verde shearwaters and Bulwer's petrels presenting the richest mite communities (eight species each). This number is in line with mite richness documented in other groups of birds, including seabirds (Fitzpatrick and Threlfall, 1977;Doña et al, 2016). For instance, other procellariiform seabirds are known to harbor more than one mite species: Puffinus gravis (nine), Oceanodroma leucorhoa (eight), and Puffinus tenuirostris (seven) (Bourgeois and Threlfall, 1979;Doña et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Although little is known about pathogen pressures in our storm-petrel population, the frequency of the most common allele of each gene (0.431 and 0.569) is higher than what Ejsmond et al (2010) found under simulations of heterozygote advantage alone, and instead is more consistent with a current or historical role for selection by particular pathogens. Leach's storm-petrels have been shown to harbour feather lice and mites (Fitzpatrick & Threlfall 1977) and a hepatazoon (Merino et al 2014). Other pathogens may be probable, given the presence of a high-frequency allele at each gene, and investigation of pathogens may shed light on the likelihood of these allele frequencies shifting radically in the future.…”
Section: Discussionmentioning
confidence: 99%
“…() found under simulations of heterozygote advantage alone, and instead is more consistent with a current or historical role for selection by particular pathogens. Leach's storm‐petrels have been shown to harbour feather lice and mites (Fitzpatrick & Threlfall ) and a hepatazoon (Merino et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to feed upon a wide variety of sea birds, and its tolerance of a wide range of environmental conditions have allowed it to become established in sea bird colonies on some of the most remote oceanic islands (e.g., Heath 1977;Bergström et al 1999aBergström et al , 1999bHänel and Heyne 2008;Heath et al 2011) and the Antarctic Peninsula (Benoit et al 2007). Ixodes uriae has been frequently reported in Canada (Bequaert 1945;Gregson 1956;Spencer 1960;Main et al 1973;Threlfall 1974, 1975;Main et al 1976b;Fitzpatrick and Threlfall 1977;Ballard and Ring 1979;Morbey 1996;McCoy et al 2001McCoy et al , 2003aMcCoy et al , 2003bJones 2004, 2007). In recent years, there has been important work done on the genetics of different I. uriae populations, including populations in Canada, which have ramifications on its ecology (McCoy and Tirard 2000;McCoy et al 2003;de Meeûs et al 2007).…”
Section: Natural Historymentioning
confidence: 99%